Impact of Increased Frequency Excitation System on Stability of Synchronous Generator - Jonaitis, A. (Elektronika ir Elektrotechnika, 2013)
The paper presents a modified classic dynamic model of synchronous generator connected to infinity bus. The model allows to use dynamic models of excitation systems containing field voltage and field current inputs for investigation of electromechanical transient processes of power system. This model was used for analysis of dynamic characteristics of synchronous generator with increased frequency excitation system according to small perturbation and eigenvalues methods. The influence of parameters of external electrical network on quality of transient processes is estimated. The transfer function of the synchronous generator with increased frequency excitation system is explored according to eigenvalues analysis method. According to the suggested methodic, stability margins of Lithuanian power plant are evaluated for different operating conditions of the generator. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.2578